2017
DOI: 10.1038/srep40372
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen related receptor is required for the testicular development and for the normal sperm axoneme/mitochondrial derivatives in Drosophila males

Abstract: Estrogen related receptors (ERRs), categorized as orphan nuclear receptors, are critical for energy homeostasis and somatic development. However, significance of ERRs in the development of reproductive organs/organelles/cells remain poorly understood, albeit their homology to estrogen receptors. In this context, here, we show that knockdown of ERR in the testes leads to improperly developed testes with mis-regulation of genes (aly, mia, bruce, bam, bgcn, fzo and eya) involved in spermatogenesis, resulting in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…Finally, Esrrb could be indirectly contributing to germline development by exerting a function in somatic gonadal tissues. A recent study using drosophila as a model to evaluate the effect of depleting genes linked to azoospermia in human males , revealed a role for ERRs in testis morphogenesis . Nonetheless, it should be pointed out that during murine development, Esrrb expression in the gonads is confined to PGCs .…”
Section: The Role Of Esrrb During Development Lessons From Ko Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Esrrb could be indirectly contributing to germline development by exerting a function in somatic gonadal tissues. A recent study using drosophila as a model to evaluate the effect of depleting genes linked to azoospermia in human males , revealed a role for ERRs in testis morphogenesis . Nonetheless, it should be pointed out that during murine development, Esrrb expression in the gonads is confined to PGCs .…”
Section: The Role Of Esrrb During Development Lessons From Ko Studiesmentioning
confidence: 99%
“…males [64], revealed a role for ERRs in testis morphogenesis [65]. Nonetheless, it should be pointed out that during murine development, Esrrb expression in the gonads is confined to PGCs [41].…”
mentioning
confidence: 99%
“…Mutations in ERR are lethal in larval development, indicating that the gene plays an essential function. A recent study showed that ERR is required for normal spermatogenesis in the fly [197], but the essential function remains undescribed. ERR orthologs are present in Lophotrochozoa and Echinodermata, but were apparently lost from nematode lineages.…”
Section: Err (Nr3b)mentioning
confidence: 99%
“…In invertebrates, only one ERR has been discovered thus far ( Sluder, Mathews, Hough, Yin, & Maina, 1999;Dehal et al, 2002;Sullivan & Thummel, 2003;Thomson, Baldwin, Wang, Kwon, & LeBlanc, 2009). A study has shown that ERR may be related to male fertility in Drosophila melanogaster (Misra et al, 2017). In crustaceans, a unique ERR gene has been found in the crab Scylla paramamosain (GenBank: GU290313.1) and Portunus trituberculatus (GenBank: KM189915.1), but reports on the function of ERR in crustaceans are rare.…”
Section: Molecular Characterization Of Estrogen-related Receptor (Errmentioning
confidence: 99%